Metastatic melanoma of the stomach - Rocha,Marcelo Eustáquio (2008)
BACKGROUND: Metastatic melanoma of the stomach is a relatively rare entity with an unusual diagnosis during life. Surgery is the treatment of choice once it alleviates the symptoms in over 90% of the cases and increases the long-term survival. CASE REPORT: A 50y woman had presented a dark spot in the ungual bed of her right-hand thumb for two years, evolving into ulceration and bleeding. The biopsy diagnosed ungual malanocytic neoplasia compatible with lentiginous melanoma confirmed by immunohistochemistry, which presented positive pigmented HMB-45 cells. After an year and a half, the patient developed metastasis of the melanoma on her left thigh and extensive ulcerated lesion in the small gastric curvature, whose biopsy was compatible with metastatic melanoma of the stomach. The hemogram found discrete anemia (Hb: 11.1 and Ht: 33%) and LDH: 333 U/L. The patient underwent total gastrectomy with reconstruction in Roux-en-Y. There was a good evolution and on the 6th post-operative day, she was discharged home. At present, in the 12th month of follow up, the patient remains without complaints, with full relief of symptoms and all normal control exams. CONCLUSION: Surgical management should always be considered for the metastatic melanoma of the gastrointestinal tract, since the procedure shows low morbidity and mortality, besides providing relief of symptoms with the improvement of the quality of life and increase in the long-term survival.